Naturally Occurring IgG Autoantibodies to Platelet Cytoskeleton Tropomyosin - Hou, Ming; Stockelberg, Dick; Kutti, Jack; Wadenvik, Hans (Thrombosis and Haemostasis, 1996)
We have observed that naturally occurring serum antibodies generated a 30 Kd band in a platelet immunoblot assay. The target protein had the same molecular weight (30 Kd) under nonreduced and reduced electrophoretic conditions, and could be immunoblotted from either autologous or homologous platelet lysates. Also, the 30 Kd reactive autoantibodies could be totally adsorbed by platelet cytoskeletons. From these data one likely candidate for the autoantibody target was the intracellular platelet protein tropomyosin. Indeed, a commercially available monoclonal antitropomyosin antibody reacted with proteins comigrating with this 30 Kd band; affinity purified human platelet tropomyosin was bound by the antibodies that recognized the 30 Kd protein. This body of evidence conclusively demonstrated that naturally occurring serum autoantibodies reacted with the platelet cytoskeleton protein - tropomyosin. These tropomyosin specific antibodies were found in roughly the same percentage of sera from patients with chronic idiopathic thrombocytopenic purpura (ITP) as from normal individuals.